A Bio‐Chemosynthetic Approach to Superparamagnetic Iron Oxide–Ansamitocin Conjugates for Use in Magnetic Drug Targeting. Issue 10 (25th January 2017) - Wang, Liang‐Liang; Balakrishnan, Asha; Bigall, Nadja‐Carola; Candito, David; Miethe, Jan Frederick; Seidel, Katja; Xie, Yu; Ott, Michael; Kirschning, Andreas
Abstract: A combination of mutasynthesis using a mutant strain of A. pretiosum blocked in the biosynthesis of amino‐hydroxybenzoic acid (AHBA) and semisynthesis relying on a Stille cross‐coupling step provided access to new ansamitocin derivatives of which one was attached by a thermolabile linker to nanostructured iron oxide particles. When exposed to an oscillating electromagnetic field the resulting iron oxide/ansamitocin conjugate 19 heats up in an aqueous suspension and the ansamitocin derivative 16 is released by means of a retro‐Diels–Alder reaction. It exerts strong antiproliferative activity (IC50 =4.8 ng mg −1 ) in mouse fibroblasts. These new types of conjugates have the potential for combating cancer through hyperthermia and chemotherapy using an electromagnetic external trigger. Abstract : Hot and toxic ! The combination of muta‐ and semisynthesis yields a modified toxic ansamitocin, which was loaded to functionalized superparamagnetic, nanostructured particles. The toxin (IC50 in the lower nanomolar range) was released in an external electromagnetic field through inductive heating. The conjugate concept allows the combination of hyperthermia with chemotherapy in anticancer research.